2016
DOI: 10.1590/1809-4430-eng.agric.v36n3p469-481/2016
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade da brachiaria irrigada no outono/inverno

Abstract: RESUMO:Um dos fatores que determinam os baixos índices zootécnicos na pecuária brasileira é a estacionalidade da produção das plantas forrageiras tropicais. A irrigação pode proporcionar aumento e estabilização da produtividade durante o outono e o inverno. Objetivou-se pelo presente estudo avaliar: a) a produtividade de massa seca e qualidade de forragem de Brachiaria brizantha, em função de lâminas de irrigação, no período do outono e do inverno; b) a umidade do solo e a temperatura do ar a fim de determinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
2
8
0
2
Order By: Relevance
“…Furthermore, we observed a gradual increase in herbage quality in 2014, which occurred due to the increased TSW rates applied. Similar results were obtained by Dantas et al (2016). Foliar analysis showed that the reference treatment (E3) had an ideal CP content, albeit below average, for every season except fall-winter.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, we observed a gradual increase in herbage quality in 2014, which occurred due to the increased TSW rates applied. Similar results were obtained by Dantas et al (2016). Foliar analysis showed that the reference treatment (E3) had an ideal CP content, albeit below average, for every season except fall-winter.…”
Section: Methodssupporting
confidence: 81%
“…Fertigation control was in accordance with plant nutritional demand, according Dantas et al (2016), and consisted of 15 kg ha -1 nitrogen (N), 3.5 kg ha -1 phosphorus (P) and 18 kg ha -1 potassium (K) per dry biomass megagram (Mg). However, water demand followed the FAO 56 method in the reference treatment (E3), which was considered the criterion of greatest value within a 28-day interval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate change have been causing direct effects on grasses in the last decades (Raz-yaseef et al, 2015;Barbosa, 2016;Kalaugher et al, 2017), including changes in rainfall patterns that may lead to a considerable decline in agricultural production (Mall, Gupta and Sonkar, 2017), causing the seasonality of the production of tropical plants (Dantas et al, 2016), common in various regions of Brazil (Gomes et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that irrigated grasslands may have higher and more stable rates of yield [6][7][8]. However, achieving high output yields with less irrigation in an efficient and sustainable manner is one of the key challenges in artificial grasslands in arid areas.…”
Section: Introductionmentioning
confidence: 99%